2015
DOI: 10.1111/jocd.12173
|View full text |Cite
|
Sign up to set email alerts
|

Biorevitalizing effect of a novel facial serum containing apple stem cell extract, pro‐collagen lipopeptide, creatine, and urea on skin aging signs

Abstract: SummaryBackground: Epithelial regeneration in skin is achieved by the constant turnover and differentiation of keratinocytes. Epidermal and dermal stem cells compartments are fundamental for the continuous renewal of the skin. Adult stem cells are the unique source for skin tissue renewal. Plants have stem cells and plant derived stem cell extracts are now used in topical products for their potential anti-ageing and antiwrinkle effects. A new dermocosmetic product containing apple stem cell extract, urea, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Scientific RepoRtS | (2020) 10:14951 | https://doi.org/10.1038/s41598-020-71351-w www.nature.com/scientificreports/ is usually related with their antioxidant properties and the content of phenolic compounds [59][60][61] . Facial serum containing apple stem cell extract reduces the mitochondrial ROS production in human senescent cultured fibroblasts 62 . Many of the phenolics present in apple peel extract were tested for their protective activity against oxidative stress in human skin fibroblast.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific RepoRtS | (2020) 10:14951 | https://doi.org/10.1038/s41598-020-71351-w www.nature.com/scientificreports/ is usually related with their antioxidant properties and the content of phenolic compounds [59][60][61] . Facial serum containing apple stem cell extract reduces the mitochondrial ROS production in human senescent cultured fibroblasts 62 . Many of the phenolics present in apple peel extract were tested for their protective activity against oxidative stress in human skin fibroblast.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoyl tripeptide‐38 belongs to a group of synthetic peptides modeled on repair signaling sequences to increase the proliferation of collagen, elastin, proteoglycan, glycosaminoglycan, and fibronectin for improvements in pigmentation, fine lines, and wrinkles in photodamaged skin. Studies of palmitoyl tripeptide‐38 in topical solutions with additive ingredients have suggested beneficial effects, including significant increases in dermal density and elasticity, as well as improvements in rhytides 11,12,20,21 …”
Section: Discussionmentioning
confidence: 99%
“…More recently, the effects of long term topical application of a serum containing urea and other actives (Peptides and pro‐collagen) have been shown to reduce the signs of cutaneous ageing in terms of improvement of the dermal density measured by high‐frequency ultrasound and mechanical properties (skin elasticity) 30 . The clinical data well correlated with the in vitro data based on the ROS production generated by the formulation.…”
Section: In Vivo Studiesmentioning
confidence: 63%